Seberapa Baik Pengetahuan Dasar Kesehatan Reproduksi Siswa Sekolah Dasar? - Dewi, Kadek Ayu CIntya (Griya Widya: Journal of Sexual and Reproductive Health, 2023)
Background: The 2007 Indonesian Adolescent Reproductive Health Survey highlights limited knowledge among adolescents regarding pubertal signs, often recognizing only physical changes. The purpose of this study is to reveal basic knowledge of reproductive health in adolescents at Ward 1 State Elementary School, Kediri City. Method: A preliminary study conducted on December 16, 2017, at Public Elementary School Bagsal 1, Kediri City, involved 15 sixth-grade respondents. Findings indicated that 11 respondents (73.3%) lacked knowledge on changing sanitary pads, and 12 respondents (80%) were unaware of risky sexual behaviors. Result: Reproductive health encompasses physical, mental, and social well-being necessary for reproductive processes, including reproductive capacity and successful childbirth, pivotal in the transition to adulthood. It often brings about various physical changes, such as increased height, body muscle, acne, the growth of hair in the armpits and genitals, the growth of breasts, changes in voice, and the growth of a mustache in boys. Implication: The findings underscore the critical need to enhance reproductive health education among adolescents in elementary schools. Addressing gaps in knowledge about puberty signs, menstrual hygiene, and risky sexual behaviors is crucial to promoting informed decision-making and healthy behaviors among young individuals. Educators and health practitioners play pivotal roles in providing accurate information and fostering open discussions to empower adolescents with essential knowledge for their reproductive health.